Evaluation of the Implementation of the â€œSIMPUSâ€ Dental Medical Record and Human Identification System in Semarang City - Sukendro, Sulur Joyo; Cahyati, Widya Hary; Rahayu, Sri Ratna; Suhito, Hanif Pandu (Jurnal Kesehatan Gigi, 2025)
The evaluation of the "SIMPUS" software in Semarang City is motivated by the existence of a dental medical record information system within the â€œSIMPUSâ€ application. However, some menus are not yet aligned with the required standards. In addition, there is a new discourse on the use of dental data as a means of human identification in disaster events. The aim of this study is to provide an overview of the implementation of a standardized dental medical record information system, as well as to establish and test a system capable of supporting decision-making in human identification. This research employed a quantitative descriptive method to evaluate the use of the â€œSIMPUSâ€ software in Semarang City. Data collection was carried out through interviews and observations. The research subjects were dental therapists and dentists at community health centers (puskesmas) within the jurisdiction of the Semarang City Health Office. Data were analyzed using a quantitative descriptive approach. The results showed that the â€œSIMPUSâ€ software in Semarang City is user-friendly as a Dental Medical Record Information System, although some codes occasionally do not appear. The system is comprehensive, and the data output matches the input provided. However, the feature for human identification using dental charts is not yet available, and there is no display of individual baseline data related to odontogram codes. The â€œSIMPUSâ€ software in Semarang City is accepted by users as a Dental Medical Record Information System that meets national dental record standards. It can be used by community health centers to manage patient registration data, medical records, and generate monthly disease reports (LB1) and dental treatment reports. However, patient search features based on odontogram codes are not yet available, and further research is needed.